Soft CP violation in K-meson systems - Montero, J. C.; Nishi, C. C.; Pleitez, V; Ravinez, O.; Rodriguez, M. C. (American Physical Soc, 2006)
We consider a model with soft CP violation which accommodates the CP violation in the neutral kaons even if we assume that the Cabibbo-Kobayashi-Maskawa mixing matrix is real and the sources of CP violation are three complex vacuum expectation values and a trilinear coupling in the scalar potential. We show that for some reasonable values of the masses and other parameters the model allows us to explain all the observed CP violation processes in the K-0-(K) over bar (0) system.